Karakteristik Habitat Larva Anopheles spp. di Desa Sungai Nyamuk, Daerah Endemik Malaria di Kabupaten Nunukan, Kalimantan Utara - Sugiarto Sugiarto; Upik Kesumawati Hadi; Susi Soviana; Lukman Hakim (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2016)
Sebatik Island, Nunukan District, North Kalimantan Province, lies on the border of Indonesia and Malaysia. Sebatik Island is one of the malaria endemic regions in Nunukan District. In 2013, 61 people in Sungai Nyamuk Village tested positive for Plasmodium falciparum from a population of 7,525 people with an of API 8.11 per 1,000 population. A research about habitat characteristics of Anopheles spp. larvae was done in Sungai Nyamuk Village, Nunukan District, North Kalimantan Province from August 2010 to January 2012. This research aimed to analyse the characteristics of breeding places of Anopheles spp. The larvae wastaken from various types of breeding places with detention and rearing until adult mosquitoes, and identified using larvae identification key. The results showed that there were four types of potential breeding places of Anopheles spp. ie lagoon, ditches, unused fish ponds and marshes. Overall, larvae of Anopheles spp. comprising five species, namely An. vagus, An. subpictus, An. sundaicus, An. indefinitus and An. peditaeniatus. Types of potential breeding places were dominated by the unused fish pond, with standing water and muddy substrate, located around settlements surrounded by grasses, shrubs and trees. The unused fish pond containedof aquatic plants such as grasses and moss. Predators were found such as of a dragonfly nymph, crustaceans, tadpoles and small fish. The unused fish pond was a potensial breeding places Anopheles spp. and important for malaria vector borne diseases in Sungai Nyamuk Villages. Early malaria vector control at larval stage was a critical point of the success of malaria elimination programs in endemic areas.